Kurikuler Mulok Perikanan Untuk Mengembangkan Literasi Laut Siswa Melalui Program Mandiri Kampus Mengajar VII 2024 - Nur Indah Yanti; Fitri Indah Yani; Nurul Mutmainnah; Nadar Nadar; Mayasari Yamin (Pakis Journal Institute, 2024)
One the campus placement schools teaching class VII 2024 is UPT SD Negeri 182 Pinrang, located at jln.H. Kanebo No.1 Ujung Lero, Suppa sub-district, Pinrang district, South Sulawesi. Lero village is in the coastal area and is known as a maritime community whose source of income or livelihood is the majority of the population as fisherman and their income comes from the sea. As om of the school located at the tip of lero, the aim of this service is to increase students marine literacy who are expected to be able to understand and evaluate every from of activity or activity in the fisheries sektor by teaching basic concepts through curricular activities, namely local fisheries content. The learning media used are learning videos and the implementation of pre-test and post-tests to determine the level of students understanding of the learning outcomes. Based on the results of the pre-test and post- test, about fisheries mulok has increased their knowledge and understanding of marine literacy.